2022
DOI: 10.1029/2022ja030751
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to Loss Across the Magnetopause During an Electron Dropout Event

Abstract: The outer radiation belt can be dramatically altered by dropout events, which deplete electron fluxes by up to several orders of magnitudes in a few hours or even less (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…This scattering can be modeled statistically in terms of a Fokker-Planck equation and it is observational signature is a diffusive flattening of the distribution function along the radial distance L * . With the first and second adiabatic invariant conserved, particles carried closer to Earth gain energy through a betatron process (Kulsrud 2005) as they sample a larger magnetic field, whereas particles diffusing to higher radial distances sample a weaker magnetic field, lose energy, and experience a greater likelihood of losses at the outer magnetopause boundary (Turner et al 2012;Hudson et al 2014;George et al 2022).…”
Section: Motivation and Backgroundmentioning
confidence: 99%
“…This scattering can be modeled statistically in terms of a Fokker-Planck equation and it is observational signature is a diffusive flattening of the distribution function along the radial distance L * . With the first and second adiabatic invariant conserved, particles carried closer to Earth gain energy through a betatron process (Kulsrud 2005) as they sample a larger magnetic field, whereas particles diffusing to higher radial distances sample a weaker magnetic field, lose energy, and experience a greater likelihood of losses at the outer magnetopause boundary (Turner et al 2012;Hudson et al 2014;George et al 2022).…”
Section: Motivation and Backgroundmentioning
confidence: 99%
“…The latter mechanism called magnetopause shadowing (MPS), which is the focus of this study, has been proved to be responsible for the fast losses of both radiation belt electrons and ring current protons (e.g., George et al., 2022; Kang et al., 2018; Liemohn et al., 1999; Staples et al., 2022; Tu et al., 2014), but its relative role in the simultaneous dropout of these two populations has not been well quantified compared to other loss processes. For radiation belt electrons, Tu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a great number of both observational and modeling studies having successfully explained the physical processes during electron flux dropouts in different events (e.g., Bortnik et al., 2006; Drozdov et al., 2019, 2022; George et al., 2022; Kang et al., 2018; Su et al., 2016; Tsurutani et al., 2016; Tu et al., 2014, 2019; Turner, Shprits, et al., 2012; Turner et al., 2014; Xiang et al., 2017; Zhang, Li, Ma, et al., 2016; Zhang, Li, Thorne, et al., 2016), only a limited number of studies systematically investigated the statistical distributions of the outer belt electron flux dropouts and their dependence on energies, various geomagnetic indices, and solar wind parameters. Several studies have demonstrated the important impact of the high solar wind dynamic pressure (P SW ) and southward interplanetary magnetic field (IMF) B z on producing significant electron flux dropouts (e.g., Gao et al., 2015; Gokani et al., 2022; Onsager et al., 2007; Yuan & Zong, 2013).…”
Section: Introductionmentioning
confidence: 99%